(untitled) (Research, Society and Development, 2022)
The present study aimed to observe the rheological behavior of goat milk at different concentrations (20, 25, 30, 35 and 40%), subsequently evaluating which concentration is most suitable for the milk drying process. It was observed that at all milk concentrations, the shear stresses are low and increase when the strain rate also increases. Such behavior is typical of a non-Newtonian fluid. This fact occurs mainly at the 40% concentration, which is the one with the highest viscosity. It is clear that a higher concentration requires a higher stress to initiate the flow, since the initial shear stress is a function of the concentration. It was also observed that the more concentrated milk will have the flow in the pumps of the drying process more difficult, requiring more energy to travel. It was observed that the three adjustment models analyzed, Bingham, Ostwald-waelw and Herschel-Buckley can be used for the product in question, as they all reached excellent R², above 0.99, with Ostwald-waele being the one that presented even better results. The flow index (n), in the Ostwald-waele model, did not show large variations between concentrations, ranging from 1.295 to 1.469, however, always higher than 1, which indicates that the fluid is considered to be dilating. It was also noticed that with the increase in concentration, there is a distancing of the values of n from the unit, deviating from the ideal.